Hippocampal CA1 Neurons Represent Positive Feedback During the Learning Process of an Associative Memory Task - Takamiya, Shogo; Shiotani, Kazuki; Ohnuki, Tomoya; Osako, Yuma; Tanisumi, Yuta; Yuki, Shoko; Manabe, Hiroyuki; Hirokawa, Junya; Sakurai, Yoshio (Frontiers in Systems Neuroscience, 2021)
The hippocampus is crucial for forming associations between environmental stimuli. However, it is unclear how neural activities of hippocampal neurons dynamically change during the learning process. To address this question, we developed an associative memory task for rats with auditory stimuli. In this task, the rats were required to associate tone pitches (high and low) and ports (right and left) to obtain a reward. We recorded the firing activity of neurons in rats hippocampal CA1 during the learning process of the task. As a result, many hippocampal CA1 neurons increased their firing rates when the rats received a reward after choosing either the left or right port. We referred to these cells as “reward-direction cells.” Furthermore, the proportion of the reward-direction cells increased in the middle-stage of learning but decreased after the completion of learning. This result suggests that the activity of reward-direction cells might serve as “positive feedback” signal that facilitates the formation of associations between tone pitches and port choice.